ANALISIS LEAN MANUFACTURING DENGAN METODEWASTE ASSESSMENT MODEL UNTUK ELIMINASI WASTE PADA PROSES PERAWATAN LAMBUNG KAPAL TONGKANG 713 PST (300FT) - Niken Yuli Kusumawati (2023)
PT Pancaran Samudra Shipyard is a place that can also be called a ship repair shop whose object of work is in the form ship maintenance and repair. Looking at the graph over the past 1 year, the delay time is still quite high and exceeds the normal processing time of 2 months. Therefore, a lean approach is needed to improve the efficiency of the ship maintenance process which is useful for the progress of PT Pancaran Samudra Shipyard. To support the analysis, it is necessary to conduct interviews and direct observations. Then, using the WAM (Waste Assessment Model) method. Assisted by the VALSAT (value stream analysis tool) method used as a tool to assist in detailed mapping with value streams that focus on the flow of value adding processes. Based on the results of data processing, the highest waste results were obtained, namely waste defects, motion and waiting. The RPN value for waste defects is 81, waste motion is 56, and waste waiting is 42.